PERAN PENDIDIKAN DAN PELATIHAN PERANGKAT DESA DALAM MENINGKATKAN KUALITAS PEMBANGUNAN INFRASTRUKTUR - Anggraini, Dewi Sinta; Puspitarini, Renny Candradewi; Septiandika, Verto (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2024)
Through education, theoretical understanding and decision-making skills can be improved, enabling individuals to recognize their responsibilities through guidance, experience sharing, and job-related training in infrastructure development planning. Previous research shows that the higher the level of education of village officials, the better their performance, which in turn improves how development is planned. However, in Pohsangit Lor Village, Wonomerto District, village officials have varying levels of education, the majority at high school level with the highest education being Bachelor's Degree, which influences the optimization of infrastructure development performance. This research aims to examine the role of education in influencing infrastructure development planning in Pohsangit Lor Village. The method used is explanatory qualitative research, which aims to explain the relationship between education and development planning. To guarantee source triangulation and triangulation techniques are used to guarantee the correctness of the data. researcher. A total of 3 researchers and 10 informants from village elements were involved in a Limited FGD. The results show that education of village officials plays an important role in ensuring targeted planning and according to the village budget. Although there are challenges in training participation, capacity building through continuing education is essential for successful village infrastructure development.